2008
DOI: 10.12968/bjca.2008.3.3.28651
|View full text |Cite
|
Sign up to set email alerts
|

Vascular access and cardiac complications after PCI: In- and out-of-hospital outcome issues

Abstract: Background: Despite the rapid increase in percutaneous coronary intervention (PCI) rates, vascular complications remain a possible source of impaired outcomes for patients. Moreover, management of complications is an integral part of cardiac nurses’ roles and responsibilities. Aim: The aim of this quality review was to highlight the in-hospital and out-of-hospital complications up to 12 months post-discharge following PCI. Methods and Results: A review of prospectively-collected data from the Angioplasty Dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…When studies were reviewed with regard to complications developing in hospital, it was observed that there were studies which had results of complication rates close to ours (16.5%-17%), less than ours (2.9%), and more than ours (35.7%-65%) [2][3][4][5][6][7][8]. These differences between the results of studies are thought to be originating from differences in methods for providing and maintaining haemostasis, mobilization time, intervention characteristics, and methodological differences like evaluation of complications and selection criteria.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…When studies were reviewed with regard to complications developing in hospital, it was observed that there were studies which had results of complication rates close to ours (16.5%-17%), less than ours (2.9%), and more than ours (35.7%-65%) [2][3][4][5][6][7][8]. These differences between the results of studies are thought to be originating from differences in methods for providing and maintaining haemostasis, mobilization time, intervention characteristics, and methodological differences like evaluation of complications and selection criteria.…”
Section: Discussionmentioning
confidence: 88%
“…Patients should be informed about what is awaiting them, possible complication development during recovery process and how they can get appropriate support [7]. Thus, patient's anxiety can diminish and compliance to treatment can be enhanced.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other aspects which influence the children's vitality and therefore which need to be addressed are: adherence to the medications, cardiac diet and nutrition, management of the child's body weight, modification of child's lifestyles, as well as the modification of the environment. It is therefore indicated that caregivers be knowledgeable and skillful about aspects of medications such as dosages and side effects and to seek the assistance of a health care provider should the child experience side-effects from the medications ( Higgins, Thoebald, & Peter, 2008 ; Reinhard, 2008; Grubb & Newy, 2006; Travis, Bethia, & Winn, 2000; Scherbring, 2002; Bucher et al, 2001; Schumacher, Stewart, Archbold, Dodd, & Dibble, 2000 ).…”
Section: The Dynamics Objectives and The Activities For The Home-mentioning
confidence: 99%
“… 16 Training in the recovery areas should also be validated through return demonstration to ensure that nurses can correlate acute clinical changes with impending complications. 17 – 19 Finally, postdischarge teaching can be effectively conducted in the recovery setting. Percutaneous coronary intervention recovery nurses should become comfortable with one-on-one teaching sessions with their patients, where customized concerns can be addressed to promote a stronger sense of support and self-efficacy.…”
Section: Introductionmentioning
confidence: 99%